Info-entretenimento na telefonia celular: informação, mobilidade e interação social em um novo espaço de fluxos - Camila Maciel Campolina Alves Mantovani (2006)
The information era, characterized by the centralization of information processes, undergoes a new phase, due to the wireless connection provided by mobile digital technologies. Among these, the mobile phone stands out, having gone through many transformations in the past years, both in external appearance and in its functions. Currently it has gone beyond being a means for telecommunications and becomemultifunctional entertaining equipments. Mobile phones have incorporated music, images, video, texts, emails and internet access to their platforms, allowing users to immerse themselves in information and interaction processes while in movement. In this scenario, the informational market diversifies and users change in great speed.In mobile phones, aside from the mobile phoning operators, new roles emerge on the scene offering Value Added Services (VAS). For instance, companies that spread information in other media began to see the mobile phone as a new and promising multimedia vehicle for their contents. The term infotainment a merger between information and entertainment translates well the new characteristic of informationwhich has been appropriated by new technologies. The flows circulating in mobile networks are hybrid and plural and point towards the marketing of information. In this context, this research had the objective of identifying, analyzing and characterizing the social and technical implications of mobile phones in the production, organization,dissemination and reception of information. In order to do so, behaviors, activities and representations of the subjects involved in these processes was analyzed, as well as the current picture of mobile phones in Brazil and in the world. Through this analysis, we sought to comprehend the new relationships established between subject, media technology and information in contemporary times